Antarctic extreme events - Siegert, Martin J.; Bentley, Mike J.; Atkinson, Angus; Bracegirdle, Thomas J.; Convey, Peter; Davies, Bethan; Downie, Rod; Hogg, Anna E.; Holmes, Caroline; Hughes, Kevin A.; Meredith, Michael P.; Ross, Neil; et al. (Frontiers in Environmental Science, 2023)
There is increasing evidence that fossil-fuel burning, and consequential global heating of 1.1°C to date, has led to the increased occurrence and severity of extreme environmental events. It is well documented how such events have impacted society outside Antarctica through enhanced levels of rainfall and flooding, heatwaves and wildfires, drought and water/food shortages and episodes of intense cooling. Here, we briefly examine evidence for extreme events in Antarctica and the Southern Ocean across a variety of environments and timescales. We show how vulnerable natural Antarctic systems are to extreme events and highlight how governance and environmental protection of the continent must take them into account. Given future additional heating of at least 0.4°C is now unavoidable (to contain heating to the 'Paris Agreement 1.5°C' scenario), and may indeed be higher unless drastic action is successfully taken on reducing greenhouse gas emissions to net zero by mid-Century, we explain it is virtually certain that future Antarctic extreme events will be more pronounced than those observed to date.